Verruconis guizhouensis sp. nov. (Sympoventuriaceae, Venturiales) from soil in China - Shao, Qiu-Yu; Ren, Yu-Lian; Chen, Wan-Hao; Liang, Jian-Dong; Zhang, Yan-Wei; Liang, Zong-Qi; Han, Yan-Feng (Phytotaxa, 2022)
A new species of Verruconis, V. guizhouensis, isolated from the rhizosphere soil of Viola philippica is introduced. Morphological characteristics and phylogenetic analyses based on multi-locus datasets (SSU + ITS + LSU) support the establishment of the new species. Phylogenetically, V. guizhouensis formed a separated subclade which has a sister relationship to V. verruculosa, V. terricola and V. thailandica with 100% MLBS and 1.00 BYPP support values. Morphologically, V. guizhouensis is similar to its three sister species, with brown, 1-septate, constricted at the septum, verrucose conidia. However, it is clearly distinguished from these three species by the presence of intercalary conidia and ovoidal conidia.